2002
DOI: 10.1208/ps040438
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic integration in drug development and dosage-regimen optimization for veterinary medicine

Abstract: Pharmacokinetic (PK)/pharmacodynamic (PD) modeling is a scientific tool to help developers select a rational dosage regimen for confirmatory clinical testing. This article describes some of the limitations associated with traditional dose-titration designs (parallel and crossover designs) for determining an appropriate dosage regimen. It also explains how a PK/PD model integrates the PK model (describing the relationship between dose, systemic drug concentrations, and time) with the PD model (describing the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 63 publications
(82 reference statements)
3
102
0
1
Order By: Relevance
“…We showed that the plasma concentration corresponding to our estimated in vivo IC 50A value would ensure, in a canine ex vivo whole-blood assay, an inhibition of approximately 80% for body temperature and 90% for the other end points of the COX-2 isoenzyme. These results are consistent with what we observed for several other NSAIDs (i.e., that an inhibition close to 90% of the COX-2 isoenzyme is predictive of clinical efficacy) (Toutain, 2002). Thus, the kaolin model could be relevant for in vitro (ex vivo) to in vivo extrapolations.…”
Section: Discussionsupporting
confidence: 91%
“…We showed that the plasma concentration corresponding to our estimated in vivo IC 50A value would ensure, in a canine ex vivo whole-blood assay, an inhibition of approximately 80% for body temperature and 90% for the other end points of the COX-2 isoenzyme. These results are consistent with what we observed for several other NSAIDs (i.e., that an inhibition close to 90% of the COX-2 isoenzyme is predictive of clinical efficacy) (Toutain, 2002). Thus, the kaolin model could be relevant for in vitro (ex vivo) to in vivo extrapolations.…”
Section: Discussionsupporting
confidence: 91%
“…Each primary PDP has its own biological meaning under the Hill model: E max quantifies the efficacy of the antibiotic, ED 50 is an approximate measure of potency, and N describes the affinity of the drug's API for binding its molecular target in the bacterial cell. Secondary PDP represent the exact potency of the antibiotic (28,38): the doses (mg/kg per day) required in vivo to reach a net bacteriostatic effect (BD) or to kill the first log (1LKD). To calculate secondary PDP, the net bacterial growth in the absence of therapy (G ϭ CFU/g h24 Ϫ CFU/g h0 ) replaces E in equation 1 when the antibiotic action prevents bacterial growth (BD) or when it kills the first log of organisms (1LKD):…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the more shallows the curve, the greater the relationships between the rates of bacterial kill versus the ATM drug concentration. This relationship can be described using a sigmoidal Emax model, also known as the Hill model, which can be described as follows (Toutain, 2002):…”
Section: Antimicrobial Pharmacodynamic Conceptsmentioning
confidence: 99%